Retrospectives and Perspectives of Šiauliai Region Sustainable Development - Tamošiūnas, Teodoras (Applied Scientific Research, 2022)
The article deals with the topical issues of sustainable development of the state and its regions, which are typical in the scientific literature and documents at the state or international level. Much attention has been paid to Lithuania's regional sustainable development policy and its implementation, analysing state-level documents. In the context of the above-mentioned issues, important statistical highlights of the situation of sustainable development of Šiauliai region (county) in relation to other regions of Lithuania and development trends planned by the state or calculated by the author are based on statistical and factual information of documents. Here, the planned measures to reduce Lithuania's regional disparities for the European Union investment period in Lithuania in 2021-2027 are reviewed. The interpretation of the research results, summaries and conclusions are presented in the article. Keywords: sustainable development, region, regional policy, sustainable development indicators.